Posture Awareness among Fitness Practitioners - E. Paladi; N. Nicolescu-Seusan (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
The 21st century has brought with it the need for flexibility and in some places adaptability to current conditions, thus many people advocate for the practice of fitness, each with different goals. Posture, however, remains an undiscussed topic in the gym ecosystem. The purpose of this study is to identify neuro-muscular imbalances and implicitly possible postural deficiencies at the level of the spine and the main human joints.